Ab initio search for cohesion-enhancing impurity elements at grain boundaries in molybdenum and tungsten. (2nd November 2016) - Scheiber, D; Pippan, R; Puschnig, P; Romaner, L
Abstract: We report high throughput density functional theory (DFT) calculations to simulate segregation of s - and p -elements in Mo and W. First, the preference of solutes for interstitial or substitutional positions in the bulk is evaluated and then the segregation energies for the solutes to interstitial and different substitutional sites at a grain boundary (GB) and a free surface (FS) are computed. We show that several solutes change their site preference from substitutional to interstitial position upon segregation to the GB. With the segregation energies to GB and FS, the changes in cohesion can be calculated and GB cohesion enhancing solutes can be identified. The results show striking similarity for both W and Mo. In addition, we collected the available literature data from experimental and theoretical side, which we consequently compare to our results. From our results and the comparison to literature, we identify B, C and Be as potential alloying additions for an increased GB cohesion in Mo and W.